Effect of Mn-content of ER5356 welding rods on mechanical properties of Al-alloys joints - Ni, Xianpeng; Xu, Shaohua; Mu, Hua (Frontiers in Mechanical Engineering, 2024)
The study investigated the influence of Mn content in ER5356 welding electrodes on the mechanical properties of Al-alloy joints produced by gas tungsten arc welding. The effect of ER5356 welding rods with different Mn contents (0.05% and 0.15%) on joint performance was comparatively analyzed using microhardness analysis, fracture morphology observation, and tensile strength testing. The casting structure disappeared, but the aluminum-manganese (Al-Mn) diffuse phase remained. Semi-continuous casting of ER5356 (0.15% Mn) specimens resulted in a 12.8% increase in yield strength and a 3.17% increase in tensile strength compared to gravity casting. Joints made with wire containing 0.15% Mn had a slightly wider heat affected zone than those made with ER5356 (0.05% Mn). The weld exhibited an irregular shape and uneven deposition when lower welding currents were used. In the joint of the ER5356 (0.05%Mn) wire specimen, brittle fractures occurred when a 125A welding current was employed. These findings demonstrate the crucial role of the Mn element in the welding process and provide important guidelines for process improvement. In particular, these findings have significant practical implications for improving the control of welding current, enhancing welding quality, and improving the mechanical properties of welds.